Dengue Vector Surveillance in Urban Residential and Settlement Areas in Selangor, Malaysia - Chen, C.D.; Benjamin, S.; Saranum, M.M.; Chiang, Y.F.; Lee, H.L.; Nazni, W.A.; Sofian-Azirun, Mohd (Malaysian Society of Parasitology and Tropical Medicine, 2005)
Ovitrap surveillance was conducted in two urban residential areas (Taman Samudera Timur and Taman Samudera Selatan) and in a settlement area (Kampung Banjar), which is located 16 km from Kuala Lumpur city center, Malaysia. In Taman Samudera, dengue cases were reported monthly in 2003/2004. Thus, a study was initiated to determine the distribution and abundance of dengue vectors, Aedes aegypti and Ae. albopictus. The ovitrap surveillance indicated that Ae. aegypti and Ae. albopictus were present both indoors and outdoors. The residential sites had 73 - 79 of the ovitraps with just Ae. aegypti population and Kg. Banjar had 56 of the ovitraps with just Ae. aegypti. In the indoor and outdoor of the residential areas, together with the settlement area, the Ae. aegypti density was significantly more than Ae. albopictus (p < 0.05) by 3 - 50 folds. There was no significant difference in the larval numbers of Ae. aegypti between indoors and outdoors (p > 0.05), thus implicating that adult gravid female Ae. aegypti are present both indoors and outdoors and they do oviposit indoors and outdoors. Ae. aegypti can be incriminated as the principal dengue vector in the urban residential site, Taman Samudera and in the settlement area, Kg. Banjar.